2006
DOI: 10.1124/mol.105.021923
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C-β3 and -β1 Form Homodimers, but Not Heterodimers, through Catalytic and Carboxyl-Terminal Domains

Abstract: Phospholipase C-␤ (PLC-␤) isoenzymes are key effectors in G protein-coupled signaling pathways. Prior research suggests that some isoforms of PLC-␤ may exist and function as dimers. Using coimmunoprecipitation assays of differentially tagged PLC-␤ constructs and size-exclusion chromatography of native PLC-␤, we observed homodimerization of PLC-␤3 and PLC-␤1 isoenzymes but failed to detect heterodimerization of these isoenzymes. Size-exclusion chromatography data suggest that PLC-␤3 and PLC-␤1 form higher affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Mutation of conserved hydrophobic residues within the analogous dimer interface of PLCb1 were shown to impair activation by Ga q (Ilkaeva et al, 2002), and size exclusion analysis of both purified PLCb proteins and isolated distal CTDs, as well as cell-based studies, suggested the existence of dimers (Singer et al, 2002;Zhang et al, 2006). Conversely, studies of fulllength human PLCb3 found no evidence of oligomerization as assessed by size exclusion chromatography, multiangle light scattering, cryo-electron microscopy, or X-ray crystallography (Lyon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation of conserved hydrophobic residues within the analogous dimer interface of PLCb1 were shown to impair activation by Ga q (Ilkaeva et al, 2002), and size exclusion analysis of both purified PLCb proteins and isolated distal CTDs, as well as cell-based studies, suggested the existence of dimers (Singer et al, 2002;Zhang et al, 2006). Conversely, studies of fulllength human PLCb3 found no evidence of oligomerization as assessed by size exclusion chromatography, multiangle light scattering, cryo-electron microscopy, or X-ray crystallography (Lyon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The "core" of the domain, which contains some of the most highly conserved residues, is found where the Da2 helix crosses one face of the helical bundle. The entire distal CTD is stabilized primarily through coiled-coil interactions, which may have relatively low stringency for amino acid side chains, and thus could account for the low sequence conservation (Singer et al, 2002;Zhang et al, 2006;Lyon et al, 2013). The tertiary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1321N1, H9c2 and HEK 293 cells were cultured in 90% DMEM, 10% fetal bovine serum, 100 units/ml penicillin, and 0.1 mg/ml streptomycin at 37°C under 5% CO 2 in humidified air [6]. One day prior to transfection, HEK 293 cells were plated at a density of 5×10 5 cells/10 cm culture dish.…”
Section: Methodsmentioning
confidence: 99%
“…The central XY domain is highly conserved among PLC isozymes and structurally forms a catalytic TIM ( T riosephosphate i so m erase) barrel to create the catalytic pocket for PI(4,5)P 2 binding [4]. PLC-β isozymes are distinguished by a structurally unique C-tail domain (approximately 400 amino acids) that is involved in regulation by Gα q subunits [1, 5] and dimerization [6-8]. …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, homodimerization of the avian full length coiled-coil domain, the deletion avian coiled-coil domain, fulllength avian PLC-β and PLC-β 1 was corroborated by size exclusion chromatography. A second study reported that full length PLC-β 1 and PLC-β 3 homodimerized, dependent on the coiled-coil domain [114]. Dimerization was validated by size exclusion chromatography and coimmunoprecipitation.…”
Section: Coiled-coil Domain Structurementioning
confidence: 98%